Church and the Bologna Process motives, prospects, difficulties = L’Église face au processus de Bologne Motifs, perspectives, difficultés = La Chiesa e il Processo di Bologna Moventi, prospettive, difficoltà - Gałkowski, Tomasz (Philosophy & canon law, 2018)
Participation of the Holy See in the Bologna Process involves bilateral benefits, but it also causes problems connected with the necessity of adaptation of ecclesiastical higher education to the requirements of the Bologna Declaration. The hitherto experience shows that the Holy See actively has taken on the responsibility for the development of the whole process, yet leaving behind particular adaptation forms within the framework of education conducted by it.